Penerapan Model Pembelajaran Simulasi Tema Hidup Rukun Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PKN Kelas VI di SDN 1 Ayong - Sirah, Febriyanti; Krowin, Martinus M.; Mottoh, Yulmi M. (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of this classroom action research is to find out how much influence the implementation of the Simulation learning model has on improving student learning outcomes in Class VI PKN subjects at SDN 1 Ayong. The research was carried out in 2 cycles. Each research cycle consists of 4 (four) stages, namely planning, implementation, observation and reflection. The subjects of this research were 19 class VI students at SDN 1 Ayong. The data collection techniques used consisted of observation (direct observation), tests (pre-test & post-test), and field notes. There was an increase in learning outcomes using the Simulation learning model for class VI students at SDN 1 Ayong. The results of the research showed that in cycle I the classical percentage value of student learning outcomes was 62.94, then it increased in cycle II with the classical percentage value of student learning outcomes being 88.10. Meanwhile, 11 people completed individual learning in cycle I or 57.89% and 8 people did not complete it, meaning 42.11% then increased in cycle II, namely 100% all completed. So it can be concluded that through the Simulation learning model it can improve student learning outcomes in PKN subjects, especially in class VI SDN 1 Ayong.